Stoichiometric relation for extraction of thorium from acidic nitrate solutions with Cyanex272 - S Milani; M Eskandari Nasab (مجله علوم و فنون هسته‌ای, 2019)
The stoichiometric relation for the extraction of thorium(IV) from acidic nitrate solutions with Cyanex272 was investigated. The effects of the extractant and nitric acid concentrations were studied. The extracted species at three different acidities (low, middle, and high levels) were found to be [Th(NO3)(OH)3.HA], [Th(NO3)(OH)2A.HA], and [Th(NO3)4.HA], respectively, based on the slope analysis method. The results showed that the extraction of thorium follow solvation mechanism in low, 0.001 M and high, 8 M concentration Nitric acid medium. While, in the middle acid conditions, 1 M, is in the form of cation exchange. The extracted Th(IV) species contain one CYANEX 272 molecule in the all acidic ranges.